Ekspresi Seni Dan Intervensi Publik (Studi Kasus Balai Soedjatmoko Tahun 2003-Sekarang) - Satriana Didiek Isnanta (Institut Seni Indonesia Surakarta, 2008)
Talking about â€œThe Expression of Art and Public Interventionâ€ always relates to the artistâ€™s communication process as the creator of art and the enjoyer (public). Or in other words, the artwork in this case is the painting as the social medium or communication vehicle of artist idea to another people. In daily social reality, the dialogic process between the artist and public frequently encounters misconception.This results from several problems: firstly, the artwork is multi-interpretative in nature, thereby leading to varied perception; secondly, the different â€œvaluesâ€ adopted by the artist and the public; and finally, the difference between the artist and several communities in the society in defining â€œthe public spaceâ€.The three problems above will be discussed and explored in this paper. Focusing on the case study in Balai Soedjatmoko from 2003 onward, it is expected that this paper will find an agreement that can mitigate the â€œpublic interventionâ€ into the emergence of artwork in the public spaces in the future.Keywords: Artistic Expression, Social Body, and Public Space.